2008
DOI: 10.1002/mnfr.200700433
|View full text |Cite
|
Sign up to set email alerts
|

Anticancer activities of cranberry phytochemicals: An update

Abstract: Studies employing mainly in vitro tumor models show that extracts and compounds isolated from cranberry fruit (Vaccinium macrocarpon) inhibit the growth and proliferation of several types of tumor including breast, colon, prostate, and lung. Proanthocyanidin oligomers, flavonol and anthocyanin glycosides and triterpenoids are all likely contributors to the observed anticancer properties and may act in a complementary fashion to limit carcinogenesis. Possible chemopreventive mechanisms of action by cranberry ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
70
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(77 citation statements)
references
References 66 publications
3
70
0
Order By: Relevance
“…LNCaP or PC3 cells were seeded onto 96-well microplates at a density of 1ϫ10 4 cells per well in 100 ml of complete medium. After incubation for 24 h, cells were exposed to var- ious concentrations of Tan IIA (0, 12.5, 25, 50 or 100 mM) for 24 or 48 h and 40 ml of XTT (1 mg/ml in phosphate buffered saline (PBS) with 10 ml PMS) was then added to each well for 2 h. The optical density was measured using microplate reader (Tecan Group Ltd., Switzerland) at 450 nm (reference wave length 650 nm).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…LNCaP or PC3 cells were seeded onto 96-well microplates at a density of 1ϫ10 4 cells per well in 100 ml of complete medium. After incubation for 24 h, cells were exposed to var- ious concentrations of Tan IIA (0, 12.5, 25, 50 or 100 mM) for 24 or 48 h and 40 ml of XTT (1 mg/ml in phosphate buffered saline (PBS) with 10 ml PMS) was then added to each well for 2 h. The optical density was measured using microplate reader (Tecan Group Ltd., Switzerland) at 450 nm (reference wave length 650 nm).…”
Section: Methodsmentioning
confidence: 99%
“…4,5) In general, apoptosis is regulated by pro-apoptotic and antiapoptotic proteins of the Bcl-2 family and executed through caspases (or cysteine-aspartic proteases), chiefly via two major and inter-related pathways, i.e., the mitochondria-dependent "intrinsic" cytochrome c/caspase-9 pathway and the death receptor-mediated "extrinsic" caspase-8 pathway. [6][7][8] Additionally, apoptosis is controlled by various cell signaling pathways such as the phosphoinositide 3-kinase (PI3K)/AKT survival pathway, regulating apoptosis chiefly by blocking caspase-9 and the mitochondria damaging Bcl-2 family protein, Bad, through phosphorylative inactivation.…”
mentioning
confidence: 99%
“…The anti-cancer properties can be attributed to a variety of phytochemicals in cranberry, including proanthocyanidin oligomers, flavonols, anthocyanin glycosides, and triterpenoids. These phytochemicals can regulate cell apoptosis, DNA repair, and anti-inflammation (Bodet et al 2006(Bodet et al , 2007aNeto 2007b;Neto et al 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Our findings are in agreement with that of GonzalezAguilar et al [27] who reported an increase in flavonoid content in mango, on exposure to UV radiation. Nowadays, flavonoids have gained considerable interest as they are found to be very effective contributors involved in protection against cardiovascular disorder by mitigating the oxidation of LDL as well as prevention of several other degenerative diseases [28]. However, these bioactive compounds (flavonoids) are considered to be absorbed in trace amounts in vivo; thus, there is a general tendency to either increase the consumption or enhance the flavonoid content of plant sources, as this can help in increasing the intake of these essential bioactive compounds and antioxidants.…”
Section: Discussionmentioning
confidence: 99%